PSYCHOLOGICAL WELL-BEING OF ACADEMICS IN HIGHER EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Azlini Hassan; Ummi Naiemah Saraih; Ain Zuraini Zin Aris, (Journal of Human Development and Communication (JoHDeC), 2025)
Various studies have already been conducted on the issue of psychological well-being of individuals. Unfortunately, most of the previous studies were not conducted from the perspective of academics in higher education. Therefore, the present study examined a considerable number of previous studies on the psychological well-being of academics in the context of higher education. The design of the study is a systematic literature review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were applied for selection, screening and reporting. The Scopus, Web of Science (WoS), Science Direct and Google Scholar databases were used for this systematic literature review of quantitative and qualitative research published between 2018 and 2022. Based on nine studies, there are three themes related to the psychological well-being of academics, including work-family conflict, workload and teaching-research role. Consequently, further research is needed to better identify the psychological well-being of academics.